Construction of Counseling and Communication Values in Hadih Maja: An Effort to Develop Inmates` Life Skills - Oknita Oknita; Adnan Yahya; Faisal Amri (Jurnal Penelitian Medan Agama, 2025)
This study aims to identify the philosophical meanings embedded in Hadih Maja for the development of prisoners? life skills, to describe the construction of counseling that incorporates Hadih Maja values in fostering prisoners? life skills, and to explore the ethical and practical implications of counseling services grounded in Hadih Maja values for prisoners? life skills development. This research employs a qualitative approach with descriptive data. Data were collected through observation, in-depth interviews, and documentation studies. Data analysis was conducted using content analysis by identifying and classifying values contained in Hadih Maja. Subsequently, the data were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the philosophical meanings contained in Hadih Maja relevant to prisoners? life skills development include self-control and self-awareness, work ethic (vocational skills), self-reflection and emotional closeness or social skills, as well as practical competence and work-related abilities (academic skills). Second, the construction of counseling and communication that integrates Hadih Maja values is manifested in a culturally based counseling model enriched with local wisdom. Third, the ethical and practical implications of counseling services grounded in Hadih Maja values emphasize the importance of culturally responsive and non?culture-biased counseling practices, as well as the recognition of prisoners as cultural subjects who require mental development rooted in their cultural context.